Experimental method for determining the deformation of warp threads on looms - Makhmudova, Nigar (Eastern-European Journal of Enterprise Technologies, 2022)
There is a large body of theoretical and experimental research aimed at determining the warp thread deformation and tension. Analytical solutions and mathematical models of the stressed state of the warp and weft threads in the formation of fabric were proposed. In almost all studies, the deformation of the warp thread was determined separately when shedding and beating the weft. There is an experimental method for determining the deformation of warp threads, which makes it possible to eliminate some of the shortcomings inherent in the theoretical techniques. However, that method has some drawbacks, such as the low accuracy of strain measurement and the complexity of certain measuring operations, which leads to an increase in the time spent on the experiment. This paper reports a study that addresses those shortcomings by proposing to photograph the object being measured using a digital camera connected to a computer system to print the image. An electronic caliper that is used to measure the deformation of warp threads on printing paper takes into consideration a fraction of a millimeter when measuring. The proposed method makes it possible to determine with sufficient accuracy and speed the deformation of warp threads in the elastic feed system of the loom, as well as allows visual control over the changes in the deformation of warp threads in the machine. The use of this method makes it possible to reduce the time of measuring the deformation of one thread from 30‒40 seconds to 5‒7 seconds, which is 5‒6 times less than that in the existing one and provides measurement accuracy to at least one dozen mm. The results of this work could be applied to determine the warp thread deformation and tension on looms when making the main weave fabrics in order to reduce the uneven tension of the main threads, increase labor productivity, and improve the quality of the fabric.